2010
DOI: 10.1158/1078-0432.ccr-09-2638
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Classification of Non–Small Cell Lung Carcinoma Using a Novel MicroRNA-Based Approach

Abstract: Purpose: Advances in targeted lung cancer therapy now demand accurate classification of non-small cell lung cancer (NSCLC). MicroRNAs (miRNA) are recently discovered short, noncoding genes that play essential roles in tissue differentiation during normal development and tumorigenesis. For example, hsamiR-205 is a miRNA that is highly expressed in lung squamous cell carcinomas (SqCC) but not in lung adenocarcinomas. The differential expression of miRNAs could be exploited to distinguish these tumor types.Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
156
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(172 citation statements)
references
References 34 publications
12
156
1
3
Order By: Relevance
“…The clinical therapy of ADC and SCC is usually based on histopathological features (Bishop et al, 2010). However, there is an urgent need to explore special treatment of these two sub-types.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical therapy of ADC and SCC is usually based on histopathological features (Bishop et al, 2010). However, there is an urgent need to explore special treatment of these two sub-types.…”
Section: Discussionmentioning
confidence: 99%
“…Has-miR-205, which suppresses epithelial-to-mesenchymal transition, has been identified as a highly specific marker for squamous carcinoma of the lung. 147,148 A wellstudied miRNA in lung cancer is miR-21. In a group of 48 lung adenocarcinomas/squamous cell carcinomas, overexpression of mature miR-21 was found in 52% of cases compared with their corresponding non-cancerous tissues.…”
Section: Histone Modificationmentioning
confidence: 99%
“…In human cancers, including lung cancer, dysregulated miRNAs can act as oncogenes or tumor suppressors (Croce, 2009). Several groups showed that miRNA profiling allows to distinguish histological lung cancer subtypes (Lebanony et al, 2009;Bishop et al, 2010). Furthermore, specific miRNA profiles have been evaluated to predict prognosis and disease recurrence in early-stage lung cancer (Yu et al, 2008;Patnaik et al, 2010).…”
Section: Introductionmentioning
confidence: 99%